A case study analysis of a sophisticated sports doping network: Lance Armstrong and the USPS Team. (September 2016) - Bell, Peter; Ten Have, Charlotte; Lauchs, Mark
Abstract: While doping in professional sport is not new, this analysis of professional cyclist Lance Armstrong and his US Postal Service (USPS) Team and associates provides additional insight into the key attributes of a sophisticated and resilient doping network. Using network analysis software the entities, events and activities of this network are examined in detail. The paper discusses the similarities between criminal networks and sophisticated sports doping networks within the context of the Tour de France. It highlights the critical elements of this resilient dark network and the strategies it employed to facilitate illicit activities and avoid detection and prosecution for more than a decade. By examining doping-related sports activities from a network perspective, this research provides insight into the resilience, vulnerabilities and indicators of such networks.